Flourish with flowers - Singh, A K; Janakiram, T; Prasad, K V (Indian Horticulture, 2019)
The floriculture industry in India is characterized by growing traditional flowers (loose flowers) and cut flowers under open field conditions and protected environment conditions respectively. India also has a strong dry flower industry, which contributes to the overall trade. Other segments like fillers, potted plants, landscape plants, trees, palms, topiary plants, seeds and planting material, turf grass industry, and value added products also contribute a share in the overall growth of floriculture sector. The traditional flower cultivation, comprising of growing loose flowers mostly for worship, garland making and decorations, forms the backbone of floriculture in India, which is mostly in the hands of small and marginal farmers. Globalization of Indian economy and subsequent liberalization of seed act paved the way for the advent of protected cultivation in India during early 1990s.